Los nutricionistas españoles en las redes sociales: análisis de los mensajes con mayor engagement en Twitter, Facebook e Instagram1 - Dra. Flora MARÍN MURILLO,Dr. José Ignacio ARMENTIA VIZUETE,Dra. María del Mar RODRÍGUEZ GONZÁLEZ,Dr. Iñigo MARAURI CASTILLO (Fonseca, Journal of Communication, 2023)
The interest in the world of nutrition is also reflected in the field of social media. This article analyzes the activity of ten dietitians-nutritionists —Julio Basulto, Miguel Ángel Lurueña, Juan Revenga, Virginia Gómez, Lucía Martínez, Aitor Sánchez, Carlos Ríos, Gabriela Uriarte, Juan Llorca and Victoria Lozada— on Twitter, Facebook, and Instagram during the two years between July 1, 2017 and June 3, 2019. During this period, the number of contents produced by these nutritionists reached 29,655 units; that caused a total of 18,410,403 responses; which means an average of 620 per message.